The Numbers Count. (19th April 2017) - Graham, Peter A.
Abstract : Numbers Skeptics deny that when faced with a choice between saving some innocent people from harm and saving a larger number of different, though equally innocent, people from suffering a similar harm you ought to save the larger number. In this article, I aim to put pressure on Numbers Skepticism.